A grammar of Wandala - Frajzyngier, Zygmunt (Mouton grammar library, 2012)
This is the first description of a most interesting Chadic language spoken in Northern Cameroon and Northern Nigeria. The grammar provides proofs for all hypotheses concerning forms and functions grammaticalized in the language. The grammar is written in a style accessible to linguists working within different theoretical frameworks.